Carnival and Power Play and Politics in a Crown Colony - Cremona, Vicki Ann (Transnational Theatre Histories, 2018)
This book shows how Carnival under British colonial rule became a locus of resistance as well as an exercise and affirmation of power. Carnival is both a space of theatricality and a site of politics, where the playful, participatory aspects are appropriated by countervailing forces seeking to influence, control, channel or redirect power. Focusing specifically on the Maltese islands, a tiny European archipelago situated at the heart of the Mediterranean, this work links the contrast between play and power to other Carnival realities across the world. It examines the question of power and identity in relation to different social classes and environments of Carnival play, from streets to ballrooms. It looks at satire and censorship, unbridled gaiety and controlled celebration. It describes the ways Carnival was appropriated as a power channel both by the British and their Maltese subjects, and ultimately how it was manipulated in the struggle for Malta's independence.